The Chilean socio-ethno-genomic cline. (2nd April 2021) - Barozet, E.; Valenzuela, C.Y.; Cifuentes, L.; Verdugo, R.A.; Herrera, L.; Acuña, M.; Llop, E.; Moraga, M.; Berríos, S.; Di Genova, A.; Digman, D.; Symon, A.; et al.
ABSTRACT: Studies of the current Chilean population performed using classical genetic markers have established that the Chilean population originated primarily from the admixture of European people, particularly Spaniards, and Amerindians. A socioeconomic-ethno-genetic cline was established soon after the conquest. Spaniards born in Spain or Chile occupied the highest Socioeconomic Strata, while Amerindians belonged to the lowest. The intermediate strata consisted of people with different degrees of ethnic admixture; the larger the European admixture, the higher the Socioeconomic Level. The present study of molecular genomic markers sought to calculate the percentage of Amerindian admixture and revealed a finer distribution of this cline, as well as differences between two Amerindian groups: Aymara and Mapuche. The use of two socioeconomic classifications – Class and Socioeconomic Level – reveals important differences. Furthermore, Self-reported Ethnicity (self-assignment to an ethnic group) and Self-reported Ancestry (self-recognition of Amerindian ancestors) show variations and differing relationships between socioeconomic classifications and genomic Amerindian Admixture. These data constitute a valuable input for the formulation of public healthcare policy and show that the notions of Ethnicity, Socioeconomic Strata and Class should always be a consideration in policy development.